Diffusion of Cd(II), Pb(II) and Zn(II) on calcium alginate beads - Kwiatkowska-Marks, Sylwia; Miłek, Justyna; Trawczyńska, Ilona (Technical Sciences, 2019)
Effective diffusion coefficients (De) for different heavy-metal salts: Cd, Pb, Zn in calcium alginate beads were determined. Their values depend on the metal type, anion from the metal salt, and the alginate content in the beads. The results of calculations indicate a decrease in the values of De, caused by an increase in the alginate content in the alginate sorbent beads. This is in agreement with the mechanism of the diffusion process taking place in porous carriers. Experimental data were found to be in good agreement with the mathematical model, as indicated by high values of the correlation coefficient.